A Practical Tariff Methodology for Port Authorities (Global Journal of Management and Business Research, 2021)
This work describes a practical tariff model regarding public ports, using the new normative launched for the National Agency of Waterborne Transportation (ANTAQ) in Brazil. It also brings analytical elements of economic balance based on appropriate average costs in each tariff modality. Contains a complete mathematical-financial model, including a numerical, hypothetical and general example -a case study serving as a starting point for all other concrete cases.
Keywords: port tariff; pricing; port; port authorities; economic regulation